Why do monetary policies matter? An experimental study of saving and inflation in an overlapping generations model - Bernasconi, Michele; Kirchkamp, Oliver (Journal of monetary economics, 2000)
The following is an examination of experiments using an overlapping generations model, where inflation is determined by the monetary policy and by the amount of average saving within each period. A new experimental setup is used that allows us to observe more details in the process of expectation forming and to separate this process from the actual saving process. In contrast to experimental findings by Lim, Prescott, Sunder; Marimon, Spear, Sunder; and Marimon, Sunder we have found that (1) agents do not form first-order adaptive expectations; (2) subjects ‘over-save’ for precautionary reasons; and as a result (3) the so-called Friedman conjecture holds, i.e. monetary policies which are equivalent in static equilibrium exhibit different levels and different volatility with regard to inflation in the experiment. This may generate important policy trade-offs between monetary regimes. We then discuss our findings and relate them to current research on adaptive learning and the role it may have in ranking alternative monetary policies.